Characterization and structural analysis of a potent anticoagulant phospholipase A2 from Pseudechis australis snake venom. (1st March 2016) - Du, Qianyun Sharon; Trabi, Manuela; Richards, Renée Stirling; Mirtschin, Peter; Madaras, Frank; Nouwens, Amanda; Zhao, Kong-Nan; de Jersey, John; Lavin, Martin F.; Guddat, Luke W.; Masci, Paul P.
Abstract: Pseudechis australis is one of the most venomous and lethal snakes in Australia. Numerous phospholipase A2 (PLA2 ) isoforms constitute a major portion of its venom, some of which have previously been shown to exhibit not only enzymatic, but also haemolytic, neurotoxic and anticoagulant activities. Here, we have purified a potent anticoagulant PLA2 (identified as PA11) from P. australis venom to investigate its phospholipase, anticoagulant, haemolytic and cytotoxic activities and shown that addition of 11 nM PA11 resulted in a doubling of the clotting time of recalcified whole blood. We have also demonstrated that PA11 has high PLA2 enzymatic activity (10.9 × 10 4 Units/mg), but low haemolytic activity (0.6% of red blood cells hydrolysed in the presence of 1 nM PA11). PA11 at a concentration lower than 600 nM is not cytotoxic towards human cultured cells. Chemical modification experiments using p-bromophenacyl bromide have provided evidence that the catalytic histidine of PA11 is critical for the anticoagulant activity of this PLA2 . PA11 that was subjected to trypsin digestion without previous reduction and alkylation of the disulfide bonds maintained enzymatic and anticoagulant activity, suggesting that proteolysis alone cannot abolish these properties. Consistent with these results, administration of PA11 by gavage in a rabbit stasis thrombosis model increased the clotting time of recalcified citrated whole blood by a factor of four. These data suggest that PA11 has potential to be developed as an anticoagulant in a clinical setting. Highlights: Snake venoms contain components that are potential therapeutic drug leads. A phospholipase (PA11) from Pseudechis australis has potent anticoagulant activity. PA11 given by gavage to a rabbit increased blood clotting by a factor of four. Further investigations into PA11 as a therapeutic drug lead are warranted.